Penyuluhan terkait infeksi cacing di Sekolah Anak Tangguh Lombok Barat - Adelia Riezka Rahim; Rosyunita Rosyunita; Nurmi Hasbi; Wayan Sulaksmana Sandhi Parwata (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
Worm infection is a problem that can be prevented and treated through simple measures such as good sanitation practices, proper hygiene, and effective deworming treatment. This intervention is aimed at students attending Anak Tangguh School, which comprises children aged 7 to 11 years. Participants in the socialization program completed a questionnaire to assess their knowledge and habits regarding worm infections. Additionally, their height and weight were measured using a scale and stature meter. The analysis of 26 children's weight and height revealed that 22 were overweight and 10 did not meet the ideal height according to WHO standards. Following the socialization program, participants acknowledged their understanding of worm infection and its consequences, expressing their commitment to adopting a clean and healthy lifestyle.